2015
DOI: 10.1111/aor.12571
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fibroblast Cellular Ligamentization Process to Polyethylene Terepthalate Artificial Ligament by Silk Fibroin Coating

Abstract: Artificial ligaments utilized in reconstruction of anterior cruciate ligament (ACL) are usually made of polyethylene terepthalate (PET) because of its good mechanical properties in vivo. However, it was found that the deficiencies in hydrophilicity and biocompatibility of PET hindered the process of ligamentization. Therefore, surface modification of the PET is deemed as a solution in resolving such problem. Silk fibroin (SF), which is characterized by good biocompatibility and low immunogenicity in clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Jaipaew et al developed a 3D porous silk fibroin (SF)/hyaluronic acid (HA) scaffold formed by freeze-drying. The scaffold was then seeded with human umbilical cord-derived mesenchymal stem cells (HUMSCs) and cultured in the chondrogenic medium [ 63 ]. The group reported sphere complexes of cells in the porous scaffold structure that express Col2a, Agg, and Sox9 markers for chondrogenesis, suggesting accelerated differentiation and functionality of the chondrocytes [ 63 ].…”
Section: Silk Materials For Tissue Regenerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaipaew et al developed a 3D porous silk fibroin (SF)/hyaluronic acid (HA) scaffold formed by freeze-drying. The scaffold was then seeded with human umbilical cord-derived mesenchymal stem cells (HUMSCs) and cultured in the chondrogenic medium [ 63 ]. The group reported sphere complexes of cells in the porous scaffold structure that express Col2a, Agg, and Sox9 markers for chondrogenesis, suggesting accelerated differentiation and functionality of the chondrocytes [ 63 ].…”
Section: Silk Materials For Tissue Regenerationsmentioning
confidence: 99%
“…The scaffold was then seeded with human umbilical cord-derived mesenchymal stem cells (HUMSCs) and cultured in the chondrogenic medium [ 63 ]. The group reported sphere complexes of cells in the porous scaffold structure that express Col2a, Agg, and Sox9 markers for chondrogenesis, suggesting accelerated differentiation and functionality of the chondrocytes [ 63 ]. The unique 3D design in addition to the interconnected pores provided a high swelling ratio and enhanced water uptake, thereby, creating a soft and elastic characteristic mimicking the native cartilage.…”
Section: Silk Materials For Tissue Regenerationsmentioning
confidence: 99%
“…In vitro experiments showed that the adhesion and proliferation of mural fibroblasts on the surfaces of these structures are improved compared to ligaments which were not modified with the polymer [139].…”
Section: Use Of Silk Fibroin and Spidroin In Tissue Engineering And Rmentioning
confidence: 99%
“…To overcome the drawback, a lot of surface coating and biological approaches have been studied, including hydroxyapatite, hydroxypropylcellulose, silk fibroin (SF), polypeptide, and estrogen. (11)(12)(13)(14)(15)(16)(17)(18). One obstacle of surface coating is that its adhesion to the ligament is not firm enough, so it may fall off partially when the PET artificial ligament is dragged through the bone tunnel.…”
Section: Introductionmentioning
confidence: 99%